2021
DOI: 10.1016/j.nicl.2021.102572
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed temporal dynamics of episodic retrieval activity with preserved spatial activity pattern in amnestic mild cognitive impairment: A simultaneous EEG-fMRI study

Abstract: Highlights The HC and aMCI subjects showed similar retrieval success patterns in fMRI analysis. The aMCI showed diminished ERP old/new effects within the retrieval success pattern. Disturbed fMRI correlate of ERP recollection component was related to EM function. The aMCI showed disturbed cognitive processes despite of the preserved fMRI pattern.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recently, Borhani et al (2021) reported that faster working memory retrieval was significantly correlated with increased resting-state delta and theta band powers over the left parietal sites in healthy older adults. A recent simultaneous EEG-functional magnetic resonance imaging (fMRI) study observed that individuals with MCI exhibited chaotic event-related potentials during the word retrieval task while preserving the spatial activity pattern ( Shu et al, 2021 ). However, it remains obscure that whether the resting theta power is linked to the delayed recall memory in the elderly people without dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Borhani et al (2021) reported that faster working memory retrieval was significantly correlated with increased resting-state delta and theta band powers over the left parietal sites in healthy older adults. A recent simultaneous EEG-functional magnetic resonance imaging (fMRI) study observed that individuals with MCI exhibited chaotic event-related potentials during the word retrieval task while preserving the spatial activity pattern ( Shu et al, 2021 ). However, it remains obscure that whether the resting theta power is linked to the delayed recall memory in the elderly people without dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD), which is characterized by latent and progressive cognitive decline, is the most common etiology for dementia and is recognized as an urgent concern that has significant implications for both individuals and society ( Lane et al, 2018 ). Mild cognitive impairment (MCI), which is considered a transitional state between normal aging and dementia, has a conversion range of 8–15% per year ( Shu et al, 2021 ). In line with recommendations form the National Institute on Aging-Alzheimers’s Association workgroups, we use the term “MCI due to AD” to refer to the symptomatic predementia phase of AD, which suggests that MCI is a critical stage for preventive treatment for dementia ( Albert et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%